Dual pH/Redox-Responsive Mixed Polymeric Micelles for Anticancer Drug Delivery and Controlled Release - Yongle Luo; Xujun Yin; Xi Yin; Anqi Chen; Lili Zhao; Gang Zhang; Wenbo Liao; Xiangxuan Huang; Juan Li; Can Yang Zhang (MDPI AG, 2019)
Stimuli-responsive polymeric micelles (PMs) have shown great potential in drug delivery and controlled release in cancer chemotherapy. Herein, inspired by the features of the tumor microenvironment, we developed dual pH/redox-responsive mixed PMs which are self-assembled from two kinds of amphiphilic diblock copolymers (poly(ethylene glycol) methyl ether-b-poly(β-amino esters) (mPEG-b-PAE) and poly(ethylene glycol) methyl ether-grafted disulfide-poly(β-amino esters) (PAE-ss-mPEG)) for anticancer drug delivery and controlled release. The co-micellization of two copolymers is evaluated by measurement of critical micelle concentration (CMC) values at different ratios of the two copolymers. The pH/redox-responsiveness of PMs is thoroughly investigated by measurement of base dissociation constant (pKb) value, particle size, and zeta-potential in different conditions. The PMs can encapsulate doxorubicin (DOX) efficiently, with high drug-loading efficacy. The DOX was released due to the swelling and disassembly of nanoparticles triggered by low pH and high glutathione (GSH) concentrations in tumor cells. The in vitro results demonstrated that drug release rate and cumulative release are obviously dependent on pH values and reducing agents. Furthermore, the cytotoxicity test showed that the mixed PMs have negligible toxicity, whereas the DOX-loaded mixed PMs exhibit high cytotoxicity for HepG2 cells. Therefore, the results demonstrate that the dual pH/redox-responsive PMs self-assembled from PAE-based diblock copolymers could be potential anticancer drug delivery carriers with pH/redox-triggered drug release, and the fabrication of stimuli-responsive mixed PMs could be an efficient strategy for preparation of intelligent drug delivery platform for disease therapy.